Outcome of monochorionic twin pregnancy complicated by Type‐III selective intrauterine growth restriction. (2nd January 2021) - Shinar, S.; Xing, W.; Pruthi, V.; Jianping, C.; Slaghekke, F.; Groene, S.; Lopriore, E.; Lewi, L.; Couck, I.; Yinon, Y.; Batsry, L.; Raio, L.; et al.
ABSTRACT: Objective: Type‐III selective intrauterine growth restriction (sIUGR) is associated with a high and unpredictable risk of fetal death and fetal brain injury. The objective of this study was to describe the prospective risk of fetal death and the risk of adverse neonatal outcome in a cohort of twin pregnancies complicated by Type‐III sIUGR and treated according to up‐to‐date guidelines. Methods: We reviewed retrospectively all monochorionic diamniotic twin pregnancies complicated by Type‐III sIUGR managed at nine fetal centers over a 12‐year period. Higher‐order multiple gestations and pregnancies with major fetal anomalies or other monochorionicity‐related complications at initial presentation were excluded. Data on fetal and neonatal outcomes were collected and management strategies reviewed. Composite adverse neonatal outcome was defined as neonatal death, invasive ventilation beyond the resuscitation period, culture‐proven sepsis, necrotizing enterocolitis requiring treatment, intraventricular hemorrhage Grade > I, retinopathy of prematurity Stage > II or cystic periventricular leukomalacia. The prospective risk of intrauterine death (IUD) and the risk of neonatal complications according to gestational age were evaluated. Results: We collected data on 328 pregnancies (656 fetuses). After exclusion of pregnancies that underwent selective reduction ( n = 18 (5.5%)), there were 51/620 (8.2%) non‐iatrogenic IUDs in 35/310 (11.3%) pregnancies. Single IUD occurred in 19/328 (5.8%) pregnancies and double IUD in 16/328 (4.9%). The prospective risk of non‐iatrogenic IUD per fetus declined from 8.1% (95% CI, 5.95–10.26%) at 16 weeks, to less than 2% (95% CI, 0.59–2.79%) after 28.4 weeks and to less than 1% (95% CI, –0.30 to 1.89%) beyond 32.6 weeks. In otherwise uncomplicated pregnancies with Type‐III sIUGR, delivery was generally planned at 32 weeks, at which time the risk of composite adverse neonatal outcome was 29.0% (31/107 neonates). In twin pregnancies that continued to 34 weeks, there was a very low risk of IUD (0.7%) and a low risk of composite adverse neonatal outcome (11%). Conclusions: In this cohort of twin pregnancies complicated by Type‐III sIUGR and treated at several tertiary fetal centers, the risk of fetal death was lower than that reported previously. Further efforts should be directed at identifying predictors of fetal death and optimal antenatal surveillance strategies to select a cohort of pregnancies that can continue safely beyond 33 weeks' gestation. © 2020 International Society of Ultrasound in Obstetrics and Gynecology